Association of a reduction in central obesity and phosphorus intake with changes in urinary albumin excretion: The PREMIER study - Alex Chang (2018)
Background: Excess adiposity and dietary factors may be important determinants of urinary albumin excretion (UAE). Study Design: Observational analysis of PREMIER, a randomized trial designed to lower blood pressure using behavioral interventions (counseling on weight loss, healthy diet, and exercise). Setting & Participants: 481 participants with normal kidney function who provided adequate 24-hour urine collections at baseline and 6 months. Predictors: Change in waist circumference; 24-hour urine sodium, potassium, and phosphorus excretion; and protein intake estimated from urea nitrogen. Outcomes & Measurements: The primary outcome was change in log-transformed 24-hour UAE over 6 months. Results: After 6 months, the proportion of individuals with UAE ≥10 mg/d decreased from 18.7% to 12.7% (P < 0.001). Changes in mean waist circumference (-4.2 ± 6.6 [SD] cm), 24-hour excretion of sodium (-28.2 ± 71.7 mmol/d), potassium (+8.4 ± 27.8 mmol/d), phosphorus (-27.7 ± 314.1 mg/d), and protein intake (-1.7 ± 19.4 g/d) were observed. After adjustment for relevant covariates, the following variables were associated significantly with reduction in ln(UAE) in separate models: decrease in waist circumference (P = 0.001), decrease in 24-hour urine phosphorus excretion (P < 0.001), and decrease in protein intake (P = 0.01). In a multivariable model including these 3 predictors, decreases in waist circumference (P = 0.002) and 24-hour urine phosphorus excretion (P = 0.03), but not change in protein intake (P = 0.5), remained associated significantly with reduction in ln(UAE). These associations remained significant even after adjustment for changes in blood pressure and insulin resistance. Baseline UAE and metabolic syndrome modified the relationship of waist circumference with ln(UAE); specifically, individuals with higher UAE and baseline metabolic syndrome experienced greater reductions in ln(UAE) from decreases in waist circumference. Limitations: Observational study with potential for confounding. Conclusions: In adults with normal kidney function, decreases in waist circumference and 24-hour urine phosphorus excretion are associated with reductions in UAE. These findings support the rationale for clinical trials to determine whether reducing dietary phosphorus intake or waist circumference could prevent chronic kidney disease or slow its progression. © 2013 National Kidney Foundation, Inc.